Self‐esteem fully mediates positive life events and depressive symptoms in a sample of 173 patients with affective disorders. (28th November 2018) - Sarubin, Nina; Goerigk, Stephan; Padberg, Frank; Übleis, Aline; Jobst, Andrea; Erfurt, Lena; Schumann, Christin; Nadjiri, Annekatrin; Dewald‐Kaufmann, Julia; Falkai, Peter; Bühner, Markus; Naumann, Felix; et al.
Abstract : Objectives: Previous research showed that positive and negative life events influence the development of depression. However, it is less clear how life events interact with depressive symptoms and self‐esteem. Design and methods: The present study aimed to investigate the mediating effects of self‐esteem on the relationship between life events and depressive symptoms in adulthood. The Traumatic Antecedent Questionnaire, Multidimensional Self‐esteem Scale (MSWS), and Becks Depression Inventory were administered in 173 psychiatric inpatients (mean age 39.69 ± 14.56 years, ranging from 18 to 76 years). At the time of assessment, all patients suffered from depressive symptoms caused by an affective disorder (major depression, bipolar I, dysthymia). Results: Path analyses showed that the individual level of self‐esteem (measured by MSWS) fully mediated the association between positive life events and depressive symptoms. Conclusions: The current study indicates that future therapy programmes for patients with depressive symptoms could include interventions focusing on the improvement of self‐esteem, as increasing self‐esteem may be beneficial for recovery. Practitioner points: To date, this is the first study exploring the pathways from positive/negative life events to depressive symptoms. The relationship between positive life experiences and depressive symptoms was fully mediated by self‐esteem. Strengthening self‐esteem in therapy might lower the vulnerability for depression.